The Relationship Between Adjustment and Mental Health of Chinese Freshmen: The Mediating Effect of Security and the Moderating Effect of Gender - Liu Cao (Frontiers Media S.A., 2022)
During the COVID-19 pandemic, many universities are confronted with campus lockdown or even school closures to reduce the risk of infection. However, these measures pose a threat to the mental health of adolescents. In particular, freshmen who have just entered the university campus may suffer from more serious mental health risks. In this study, 1,818 freshmen were analyzed by using the Chinese College Student Adjustment Scale (CCSAS), Sense of Security Questionnaire (SQ), and Symptom Check List 90 (SCL-90) of the qualitative method. The results showed that adjustment had an impact on mental health. Firstly, there was a significant negative association between adjustment and mental health. Secondly, adjustment had a significant predictive effect on mental health. Finally, a sense of security and gender affected the relationship between adjustment and mental health. Collectively, adjustment, sense of security, and gender exerted impacts on the mental health of freshmen, suggesting that we should create a warm and harmonious campus environment for students and conduct targeted education for male and female students.